On the magnetism of grain boundary phase and its contribution to the abnormal openness of recoil loops in hot-deformed magnets. (18th December 2019) - Zhao, Lizhong; Greneche, Jean-Marc
Abstract: The magnetism of grain boundary (GB) phase plays a critical role in the coercivity of Nd–Fe–B magnets. In this work, the aggregation of the GB phase was formed in the hot-deformed magnet due to the low-density high-velocity compaction (HVC) precursor. The ferromagnetism of GB aggregation was confirmed by the analysis of 57 Fe Mössbauer spectrometry, and its correlation to the magnetic performance was investigated by micromagnetic simulation. Results show that the soft magnetic GB aggregation is responsible for the low coercivity of the hot-deformed magnet. Moreover, an abnormal large openness of the recoil loop under the reversal magnetic field H R was presented in this work, and the underlying mechanism is interpreted by introducing demagnetization energy. To compensate for the problem of low density, low-melting-point Nd70 Cu30 powders were added into the HVC magnet, which makes the GB aggregation paramagnetic and enhances the coercivity.